ChemInform Abstract: Copper‐Catalyzed Coupling of 2‐Vinyl Benzaldehydes with 3‐Alkenyl 2‐Bromocarbonyls for the Rapid Construction of 3, 4‐Cyclopenta‐1‐tetralones. Issue 37 (August 2016) - Zhu, Hui; Nie, Xingliang; Huang, Qianwen; Zhu, Gangguo
Abstract: A straightforward, efficient, and highly diastereoselective method for the construction of 3, 4‐cyclopenta‐1‐tetralones via the copper‐catalyzed cascade annulation of 2‐vinyl benzaldehydes with 3‐alkenyl 2‐bromocarbonyls is developed.